ANALISIS KUALITAS LAYANAN TERHADAP KEPUASAN DAN LOYALITASPASIEN RUMAH SAKIT SYAFIRA PEKANBARU - HIDAYAT, TAUFIK; Restuti, Sri (Jurnal Tepak Manajemen Bisnis, 2016)
A very tight competition among hospitals, the practices of midwives, physician practices,and other healthcare services, demanding RS Syafira Pekanbaru to improve the quality ofservice that can meet patientâs expectations or desire. To create a quality of service that canachieve patient satisfaction, could not be separated from the role of human resources whohave the attitude, behavior, knowledge, and ability to support the effectiveness of therealization of quality service.This study aimed to analyze the influence of the quality ofservice that consists of the quality of interaction, the quality of the physical environment,and the quality of the results of the patient satisfaction and loyalty. The sample of this studywas 75 patients from RS Syafira Pekanbaru who were hospitalized were selected accordingto the criteria in research.Data analysis using Partial Least Square (PLS). The first toseventh hypotesis was tested using path coefficient, T static, and original sample. The resultfrom this study shows that the quality of service which is the quality of interaction, has anegative effect on patient satisfaction, but the quality of interaction also have a positiveimpact on patient loyalty. The quality of the physical environment and the quality of theresults has a positive impact on patient satisfaction and loyalty. The satisfaction of patientalso has positive impact into the loyalty of patient.